2012
DOI: 10.14310/horm.2002.1384
|View full text |Cite
|
Sign up to set email alerts
|

45,X/46,XY mosaicism: a cause of short stature in males

Abstract: 45,X/46,XY mosaicism is associated with a broad spectrum of phenotypes ranging from apparently normal male development to individuals with incomplete sexual differentiation and clinical signs of Turner syndrome in both males and females. The most common presentation among individuals with a 45,X/46,XY karyotype is sexual ambiguity, accounting for approximately 60% of cases, while the least common category of 45,X/46,XY patients consists of those with bilaterally descended testes, found in 11-12%. We report on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 9 publications
2
15
0
1
Order By: Relevance
“…GH deficiency has been rarely reported in boys with 45,X/46,XY mosaicism [Efthymiadou et al, 2012]. Thus, classic GH deficiency likely does not occur in this disorder [Richter-Unruh et al, 2004], as confirmed by the normal GH response to provocative stimuli [Bertelloni et al, 2015].…”
Section: Causes Of Short Stature In Males With 45x/46xy Mosaicismmentioning
confidence: 73%
See 1 more Smart Citation
“…GH deficiency has been rarely reported in boys with 45,X/46,XY mosaicism [Efthymiadou et al, 2012]. Thus, classic GH deficiency likely does not occur in this disorder [Richter-Unruh et al, 2004], as confirmed by the normal GH response to provocative stimuli [Bertelloni et al, 2015].…”
Section: Causes Of Short Stature In Males With 45x/46xy Mosaicismmentioning
confidence: 73%
“…45,X/46,XY mosaicism is rare (0.23/1.000 amniocenteses or 1.7/10.000 newborns) [Chang et al, 1990;Huang et al, 2002], but likely underestimated; in fact, short stature, a well-known feature of these children [Gantt et al, 1980;Knudtzon and Aarskog, 1987;Telvi et al, 1999;Lindhardt Johansen et al, 2012], may be the only clinical finding, and affected boys may go unrecognized if signs of MGD are not present and/or karyotyping is not performed [Richter-Unruh et al, 2004;Lee et al, 2006;Jacobsen and Cohen, 2008;Lara Orejas et al, 2008;Efthymiadou et al, 2012].…”
mentioning
confidence: 99%
“…45,X/46,XY that sometimes referred to as mixed gonadal dysgenesis is a rare mosaicism associated with a wide range of phenotypes in both males and females, from normal cases to individuals with incomplete sexual differentiation and clinical signs of Turner's syndrome. It most probably arises through anaphase lag during mitosis (in the zygote), although Y chromosomal abnormalities and interchromosomal rearrangements with loss of structural abnormal Y material are sometimes seen, and seems to be a common mechanism for the variants (Efthymiadou, Stefanou, & Chrysis, ; Kronenberg & Williams, ). In 45,X/46,XY mosaicism cases, there is the concurrent presence of a X monosomy lineage (45,X) and another with male formation (46,XY).…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The most common presentation of 45,X/46,XY karyotype is phenotypically normal male, next being genital ambiguity. 9 The male turner syndrome is one of the rarest presentations and with its complexities calls for a through anaesthetic planning.…”
Section: Discussionmentioning
confidence: 99%